PTH-034 Hemospray may not reliably achieve hemostasis beyond 48 hours in acute upper gastrointestinal bleeding. (22nd June 2015) - Dixon, S; Tate, D; Przemioslo, R; Lockett, M
Abstract : Introduction: Hemospray (Cook labs, Birmingham, USA) has been shown in multiple case series to be a useful and effective tool 1 in the management of acute GI bleeding where existing therapies fail to achieve hemostasis 2 or are impractical. It is as yet unclear whether treatment with Hemospray provides temporary or definitive benefit. Method: We prospectively followed 9 consecutive cases in which Hemospray was used to control acute upper GI bleeding. Each case was followed to 30 days at which point the primary end-points of rebleeding and mortality were documented. Data was sourced from case notes and the local endoscopy database. All patients were treated at Southmead Hospital, Bristol, United Kingdom – a large endoscopy unit serving a population of around 620, 000. Statistical analysis was by chi-squared and unpaired t-test. Results: 9 patients (7 males, 2 females) were included in the study with a mean age of 60.1 years (range 18–86 years). Endoscopic diagnoses included duodenal ulcer (3), gastric ulcer (1), gastric tumour (1), oeosophageal varices (1), Dieulafoy lesion (1), ERCP sphincterotomy site bleed (1) and angiodysplasia (1). Hemospray was used as the only therapeutic modality in 7 cases. Hemostasis was achieved in 6/9 cases at the index endoscopy. In 3/9 cases bleeding continued: 2 patients underwent further endotherapy and 1 patient required a Sengstaken-Blakemore tube and subsequently died. 3/9 patients experienced rebleeding. 1 patient required further endotherapy and 2 patients required laparotomy. 2 patients experienced rebleeding more than 48 h after the index endoscopy. Rebleeding did not vary across the range of endoscopic diagnoses (p = 0.423) or age of patient (p = 0.302). At 30 days only 3/9 patients treated with Hemospray did not require further intervention. 8/9 patients survived to 30 days. Conclusion: Our case series indicates that apparent initial hemostasis after application of Hemospray may be a temporary outcome only. In the UK, where physicians are urged to discharge patients soon after clinical stability has been achieved, this is a particularly important message. There may be benefit from relook endoscopy at 48 h or prolonged inpatient observation although this has not been suggested elsewhere. Larger studies are required and a region-wide series is planned. Disclosure of interest: None Declared. References: Bustamante-Balén M, Plumé G. Role of hemostatic powders in the endoscopic management of gastrointestinal bleeding. World J Gastrointest Pathophysiol . 2014;5(3):284–92 Smith LA, Morris AJ, Stanley AJ. The use of hemospray in portal hypertensive bleeding; a case series. J Hepatol . 2014 Feb;60(2):457–60